2011
DOI: 10.1111/j.2042-7174.2011.00097.x
|View full text |Cite
|
Sign up to set email alerts
|

Responsible self-medication: perceived risks and benefits of over-the-counter analgesic use

Abstract: Objectives  This study examines awareness of the potential risks associated with over‐the‐counter (OTC) use of paracetamol and non‐steroidal anti‐inflammatory drugs (NSAIDs) among Australian consumers to better understand patterns of usage of these products. Methods  We employed two self‐reported cross‐sectional surveys (conducted in 2001 and 2009) using computer‐aided telephone interviewing. Both survey samples were weighted to match national population proportions; data were collected for 3702 respondents (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
89
4
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(108 citation statements)
references
References 37 publications
9
89
4
6
Order By: Relevance
“…Similar observations come from Poland study and papers of Matoulková et al and Reguła et al, where similarly around 16% of the subjects shared the same belief. [10,20,21] Our findings generally revealed no significant difference in use of analgesics between male and female as the previous study in Iran and that converse to other studies in Riyadh, Taif, turkey, Germany, and Norway. [1,14,15,17,22,23] Like our findings in Saudi, many studies have also shown there is a significant age difference in the prevalence of analgesic use among the population.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Similar observations come from Poland study and papers of Matoulková et al and Reguła et al, where similarly around 16% of the subjects shared the same belief. [10,20,21] Our findings generally revealed no significant difference in use of analgesics between male and female as the previous study in Iran and that converse to other studies in Riyadh, Taif, turkey, Germany, and Norway. [1,14,15,17,22,23] Like our findings in Saudi, many studies have also shown there is a significant age difference in the prevalence of analgesic use among the population.…”
Section: Discussionsupporting
confidence: 65%
“…The strengths include the use of a large area of the general population; it is not limited to the specific cities or level of education like other studies. [10,22,23,30,31] On the other hand, the electronically distributed questionnaire gave a great opportunity to the young female to take part in the study. Furthermore, higher education was predominating among electronically recruited individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ibuprofen in a dosage of 200 mg is OTC drug, however our patients were taking larger doses (400 mg). Larger dose of ibuprofen increases unwanted effects and exposes patient to larger risk from intestineal bleeding, chronic kidney failure etc, and of course increases the possibility of interaction [4,6,[13][14]. Number of unwanted side effects increases with taking more type of drugs and with lenght of taking them [3,6,11].…”
Section: Discussionmentioning
confidence: 99%
“…Self-medication encourages consumers to take an active role in their health. [2] In a number of developing countries, many drugs are dispensed over the counter without medical supervision. In this case, self-medication provides a lower cost alternative for people who cannot afford the cost of clinical service.…”
Section: Original Articlementioning
confidence: 99%